Antibody-enhanced cross-presentation of self antigen breaks T cell tolerance - Stephanie O. Harbers; Andrea Crocker; Geoffrey Catalano; Vivette D’Agati; Steffen Jung; Dharmesh D. Desai; Raphael Clynes (The Journal of Clinical Investigation, 2007)
We have developed a model of autoimmunity to investigate autoantibody-mediated cross-presentation of self antigen. RIP-mOVA mice, expressing OVA in pancreatic β cells, develop severe autoimmune diabetes when given OT-I cells (OVA-specific CD8+ T cells) and anti-OVA IgG but not when given T cells alone. Anti-OVA IgG is not directly injurious to the islets but rather enhances cross-presentation of apoptotic islet antigen to the OT-I cells, leading to their differentiation into potent effector cells. Antibody-driven effector T cell activation is dependent on the presence of activating Fc receptors for IgG (FcγRs) and cross-priming DCs. As a consequence, diabetes incidence and severity was reduced in mice lacking activating FcγRs. An intact complement pathway was also required for disease development, as C3 deficiency was also partially protective. C3-deficient animals exhibited augmented T cell priming overall, indicating a proinflammatory role for complement activation after the T cell priming phase. Thus, we show that autoreactive antibody can potently enhance the activation of effector T cells in response to cross-presented self antigen, thereby contributing to T cell–mediated autoimmunity.